Pengaruh Penilaian Kinerja Dan Komitmen Organisasi Terhadap Kepuasan Kerja Penyuluh Pertanian - Mila Hariani; Mochamad Irfan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2019)
Extension agents as the spearhead of extension services to farmers is a figure who has the role of developing farming and increasing agricultural yields. Extension officers are required to have the competencies expected by the organization. Implementation of competencies is monitored through performance appraisals. Regular monitoring of the work of extension agents is expected to provide future work development. Organizational commitment is a variable that plays a role in shaping job satisfaction. Extension instructors who show commitment are satisfied with their work. This research involved 35 instructors in Lumajang Regency, East Java Province. By using multiple linear regression analysis tools will be analyzed the effect of performance appraisal variables and organizational commitment on the job satisfaction of instructors partially and simultaneously. The results of this study stated that performance appraisal proved to have a significant effect on instructor job satisfaction. Organizational commitment proved to have a significant effect on job satisfaction of extension workers. Performance appraisal and organizational commitment simultaneously have a significant effect on the job satisfaction of instructors.